“En venganza del insulto que hicieron” Percepciones mapuche sobre la brujería y las relaciones interétnicas en el área arauco-pampeana (Siglos XVI - XIX) - Joaquín García Insausti (Nuevo mundo - Mundos Nuevos, 2022)
This paper aims to examine the mapuche considerations about magical aggression in the context of interethnic relations established in the arauco-pampean area. The indigenous witchcraft beliefs are an interpretative system about the origin of the misfortune which had to be adjusted to incorporate within its boundaries the wingka otherness, native denomination of the European invaders. On the subject, the historical sources provide data that would seem contradictory at first sight. On the one hand, the indigenous people consider the wingka incapable of mastering the means necessary to carry out the magical aggression. On the other the belief that certain wingka would be capable of resorting to supernatural means to unleash epidemics. We seek to analyze these sources to deepen our conception of the indigenous perception of wingka otherness and how it was incorporated into their interpretative schemes about the origin of misfortune within the ethnogenetic process triggered by the European invasion.